Perancangan Sistem Kontrol Pid Pada Segway Beroda Dua Berbasis Matlab/Simulink - Bagus Sutasoma, Anak Agung; Widhiada, I wayan; Adi Atmika, I Ketut (Teknik Desain Mekanika, 2021)
Abstract Segway is an environmentally friendly electric powered transportation, can be used indoors or outdoors, because there is no exhaust of harmful gases. In this research, how to simplify the concept of robotics on the Segway and try how to respond to the static motion of the Segway when given PID (Proportional - Integral - Derivative) control. In this test, it was carried out with the Matlab / Simulink application on the segway prototype using a PID control system with a time of 15s at a reference angle of 15 ° and - 15 °. Various PID parameters that have been trial-error in static motion experiments on the Segway. The best values were obtained, namely Kp = 10 KP, Ki = 40 KI and Kd = 0 KD. The motion data obtained are in the form of overshoot value, error percentage and settle time. overshoot is the highest peak of the reference line, error is the ratio between input and output, and settle time is the time to reach steady state. Then the results obtained from using PID control are 37.43% overshoot, 5.06% error, and 1.9s settle time at 15 °. At position - 15 °, you get 11.95% overshoot, 7.66% error and 4.6s for settle time. Keywords: Prototype, Control System, Motion Response